The reasons behind English Language instructors' quitting their MA studies - İlknur Karadağlı Dirik (Literacy Trek, 2018)
The aim of the study was to gain insight into the English language teachers who quitted their MA studies through one research question that asked the reasons that led the teachers to quit their MA. Three English language instructors participated in this purely qualitative study. I collected the data through semi-structured interviews and graphic elicitation tasks. The results showed that there were a few reasons for their decision to quit, the most important one being the lack of motivation. Implications were discussed in the paper.